ДЕНЕ МӘДЕНИЯТЫ САБАҒЫНДА МИЛЛИЙ БАЛАЛАР ОЙЫНЛАРЫН ҮЙРЕТИЎДИҢ ӘҲМИЙЕТИ - Бердибаева, Г.Ж. (FAN va JAMIYAT, 2020)
The article describes the Karakalpak national children's game "blind man's buff", methods of playing the game, the influence and significance of "blind man's buff" in the development of national identity.